Breastfeeding initiation or duration and longitudinal patterns of infections up to 2 years and skin rash and respiratory symptoms up to 8 years in the EDEN mother–child cohort. Issue 3 (22nd January 2020) - Davisse‐Paturet, Camille; Adel‐Patient, Karine; Forhan, Anne; Lioret, Sandrine; Annesi‐Maesano, Isabella; Heude, Barbara; Charles, Marie Aline; de Lauzon‐Guillain, Blandine
Abstract: This paper aimed to examine the effect of breastfeeding on longitudinal patterns of common infections up to 2 years and respiratory symptoms up to 8 years. To assess the incidence and reoccurrence of infections and allergic symptoms in the first years of life among 1, 603 children from the EDEN mother–child cohort, distinct longitudinal patterns of infectious diseases as well as skin rash and respiratory symptoms were identified by group‐based trajectory modelling. To characterize infections, we considered the parent‐reported number of cold/nasopharyngitis and diarrhoea from birth to 12 months and otitis and bronchitis/bronchiolitis from birth to 2 years. To characterize allergy‐related symptoms, we considered the parent‐reported occurrence of wheezing and skin rash from 8 months to 8 years and asthma from 2 to 8 years. Then associations between breastfeeding and these longitudinal patterns were assessed through adjusted multinomial logistic regression. Compared with never‐breastfed infants, ever‐breastfed infants were at a lower risk of diarrhoea events in early infancy as well as infrequent events of bronchitis/bronchiolitis throughout infancy. Only predominant breastfeeding duration was related to frequent events of bronchitis/bronchiolitis and infrequent events of otitis. We found no significant protective effect of breastfeeding on longitudinal patterns of cold/nasopharyngitis, skin rash, or respiratory symptoms. For an infant population with a short breastfeeding duration, on average, our study confirmed a protective effect of breastfeeding on diarrhoea events in early infancy, infrequent bronchitis/bronchiolitis and, to a lesser extent, infrequent otitis events up to 2 years but not on other infections, skin rash, or respiratory symptoms4. Abstract : In an infant population with a short breastfeeding duration and using longitudinal patterns of infection, skin rash and respiratory symptoms, on average, our study confirmed a protective effect of breastfeeding on diarrhea events in early infancy, infrequent bronchitis/bronchiolitis and, to a lesser extent, infrequent otitis events up to 2 years but not on cold/ nasopharyngitis, skin rash or respiratory symptoms.